Working Through Asymmetries of Knowledge and Expertise in a «Giving Back to the Field» Session (Foro de Educacion, 2019)
This article examines a «giving back to the field» experience in a state-funded faith school in Catalonia (Spain), where we conducted ethnographic fieldwork on the introduction of English as a vehicular language in compulsory schooling. After two years of observing pre-school, primary and secondary education classes, attending meetings, and interviewing teaching staff and administrators, we were asked by the primary school coordinator to hold a training session in June 2017 as university «experts» acquainted with the institutional context. The school had been teaching extra hours of a subject taught in English named Science, but teachers were only partially satisfied with the results. In addition, an educational consultant that the school had recently hired had suggested that these Science classes needed to be reformulated. In this paper, we shall trace the preparatory email messages that we exchanged with the primary school coordinator, as well as the discursive development of the two-hour face-to-face session, which was attended by over fifteen teachers and which we audio recorded. We discursively dissect the ways in which a shared understanding of the problem and of possible solutions was constructed. We also analyse how expertise is enacted in interaction and contributes to the meeting outcomes. We suggest that our approach was in line with collaborative, reciprocal and transformative research paradigms drawing on the close relations with some of the participants and the in-depth knowledge of the school culture that had developed out of our two-year ethnographic engagement with the field.